Community-associated methicillin-resistant Staphylococcus aureus immune evasion and virulence - Graves, Shawna F. (2010)
Staphylococcus aureus is a significant cause of human infections globally. Methicillin-resistant S. aureus (MRSA) emerged in the early 1960s and is now endemic in most healthcare facilities. Although healthcare-associated MRSA infections remain a major problem in most industrialized countries, those caused by community-associated MRSA (CA-MRSA) are now the most abundant cause of bacterial infections in the community in some parts of the world, such as the United States. The basis for the emergence and subsequent success of CA-MRSA is incompletely defined. However, the ability of the pathogen to cause disease in otherwise healthy individuals is likely attributed, in part, to its ability to circumvent killing by the innate immune system, which includes survival after phagocytosis by neutrophils. In this review, we discuss the role of neutrophils in host defense against S. aureus and highlight progress made toward understanding mechanisms of CA-MRSA virulence and pathogenesis.